Localization of 'Candidatus Liberibacter solanacearum' (Rhizobiales: Rhizobiaceae) in Bactericera cockerelli (Hemiptera: Triozidae). (1st January 2014) - Cooper, W Rodney; Sengoda, Venkatesan G; Munyaneza, Joseph E
Abstract: ' Candidatus Liberibacter solanacearum' is a pathogen of solanaceous crops (Solanales: Solanaceae) that causes zebra chip disease of potato ( Solanum tuberosum L.) and plant dieback in tomato ( S. lycopersicum L.) and pepper ( Capsicum spp.). This pathogen is vectored by the potato/ tomato psyllid Bactericera cockerelli (Šulc) (Hemiptera: Triozidae), but little is known about the interactions between B. cockerelli and ' Ca . Liberibacter solanacearum.' Fluorescence in situ hybridization was used to assess the incidence of ' Ca . Liberibacter solanacearum' in the hemolymph, bacteriomes, alimentary canals, and salivary glands of B. cockerelli . Liberibacter was observed in 66% of alimentary canals, 39% of salivary glands, and 40% of bacteriomes dissected from adult psyllids. Compared with adults, the organs of fifth instars appeared less likely to harbor Liberibacter, which was observed in 52% of alimentary canals, 10% of salivary glands, and 6% of bacteriomes dissected from the nymphs. Results of real-time polymerase chain reaction confirmed that fewer fifth instars were infected with Liberibacter compared with adults and indicated that fifth instars were less likely to transmit the pathogen to noninfected host plants. These observations of the localization of ' Ca . Liberibacter solanacearum' in the organs and tissues of B. cockerelli adults and nymphs will aid the study of Liberibacter-psyllid interactions and the epidemiology of ' Ca . Liberibacter solanacearum.'